The impact of tax policy on the creative economy in Indonesia - Maulana, Ayang Fristia; Apriansyah, Rizki; Hidayanto, Lucki; Subardi, Dendi; Hidayat, Rahmad (Journal of Law Science, 2024)
The creative economy in Indonesia is one of the economic sectors that utilizes individual creativity, skills and expertise to create prosperity and employment opportunities by producing and utilizing intellectual property. This sector includes various industries such as performing arts, design, film, music, publishing, culinary, fashion, and many more. The creative economy also makes many positive contributions to certain sectors, for example, the creative economy contributes to the employment sector by making it a source of employment, especially for millennials to generation Z and those who have creative ideas even in the economic tourism sector. creatives also make quite a big contribution, where they are able to play a role in supporting tourism, especially in the field of arts and culture and interesting festivals, which can attract tourists. The government with its policies through the creative economy agency provides several supports, including: training and development, funding and investment, as well as promotion and marketing.